Plastic Waste Material Flow Analysis for Thailand : Summary Report - World Bank (Washington, DC, 2022)
Thailand, like many countries around the world, is in the midst of a significant plastic waste crisis. In 2019, the government of Thailand released the Roadmap for Plastic Waste Management 2018-2030 and is developing the National action plan on Marine plastic debris to alleviate the current impacts and avert future damage caused by marine plastic debris. While these efforts are critical steps toward reining in the country’s plastic pollution problem, further insight is needed into where the plastic waste comes from and how it moves in the environment. This study aims to better understand how plastic waste travels from land-based sources to marine environments by analyzing the material flow of plastic waste in five high-priority catchments. The study presents the first large-scale assessment in Thailand to integrate national waste generation and waste management performance data with actual hydrological conditions to estimate how mismanaged plastic waste is carried and discharged into the marine environment. This report is designed to assess how much mismanaged plastic waste (MPW) is flowing into the Gulf of Thailand. In Chapter 2, the approach and methodology are presented and explained, and the various definitions used in the report are discussed. The results of the models are presented in Chapter 3. The solid waste management model results are provided first, followed by the results from the fate and transport models. Chapter 4 provides the final conclusions and recommendations, which offer priority lists and examples of recommended measures to reduce marine debris.